Pharmacology and Toxicology of Opioids—Recent Advances and New Perspectives - Joana Barbosa; Ricardo Jorge Dinis-Oliveira; Juliana Faria (Pharmaceuticals, 2025)
This Special Issue of Pharmaceuticals comprises one review and four original research articles that explore the multifaceted pharmacological and toxicological profiles of both classical and atypical opioids across different clinical contexts and biological models [...]